Penerapan E-Kinerja dalam Meningkatkan Transparansi dan Akuntabilitas Aparatur Sipil Negara di Distrik Misool Timur Kabupaten Raja Ampat - Sattu Sattu; La Ode Hasanuddin; Awal Fikri (Universitas Muhammadiyah Sorong, 2026)
This study was motivated by the need to strengthen the performance management of the Civil Service through a digital system capable of enhancing transparency and accountability in work, particularly in island regions with limited infrastructure. This study aims to analyze the implementation of e-performance in enhancing the transparency and accountability of the Civil Service in East Misool District, Raja Ampat Regency. The method used is descriptive qualitative with a case study approach. Data were obtained through in-depth interviews, observations, and documentation of officials involved in the use of e-performance. Data analysis was conducted through data condensation, data presentation, as well as drawing and verifying conclusions. The research results indicate that e-performance has facilitated the more systematic recording of civil servants’ work activities, strengthened the traceability of performance reports, and supported managerial oversight of employees’ task execution. From an accountability perspective, e-performance encourages civil servants to be more responsible, as work reports serve as the basis for performance evaluation and assessment. However, its implementation remains suboptimal due to limited internet and electricity access, the archipelagic geographical conditions, and the technological capabilities of some employees. This study concludes that e-performance plays a positive role in strengthening transparency and accountability among civil servants, but requires support in the form of digital infrastructure, training for employees, and adaptive reporting mechanisms.